An estimation of the extent of cropland abandonment in mountainous regions of China. (16th April 2018) - Li, Shengfa; Li, Xiubin; Sun, Laixiang; Cao, Guiying; Fischer, Guenther; Tramberend, Sylvia
Abstract: With the wages for migrant workers increasing dramatically in China since 2003, the size of the agricultural labour forces has been shrinking rapidly. Intensively substituting agricultural machinery for the shrinking farm labour force is hardly possible for croplands in the mountainous regions of China where mechanization is difficult to achieve due to small field size and rough terrain. This has eventually led to cropland abandonment in these regions. Considering the high pressure for food security in China, cropland abandonment in the mountainous regions should not be ignored. By employing a novel method, this study estimates the extent of recently abandoned croplands (period 2000–2010) and the changes that can be expected in the future in China's mountainous areas. The results show that the total extent of abandoned croplands in Chinese mountainous counties during the period 2000 to 2010 is estimated at 147 million mu (1 mu = 666.67 m 2 ); in total, about 28% of croplands in mountainous counties was abandoned, including croplands converted in the Grain for Green Programme. With 3 scenario assumptions, a sizeable extent, 114 to 203 million mu, of croplands may be abandoned from 2010 to 2030 with the rapid decrease and ageing of projected farm labour forces. This could exacerbate the future challenges of maintaining China's food security. A substantial increase in agricultural project investments, including land consolidation and agricultural productive fixed assets, especially microtillage machines, could help mitigate the risk of cropland abandonment. Additionally, land‐use and environmental policymaking should take into account the expanding cropland abandonment in mountainous regions.